Pengembangan Media Pembelajaran Berbasis Android di SMP Negeri 1 Air Putih - Panjaitan, Engly Shintya; Sihombing, Wingston Leonard (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This research aims of determining the validity and practically of a product, a mathematical learning medium based on android developed with help of iSpring suite software and Microsoft powerpoint on Geometry for student of class VII in the State Junior High School 1 Air Putih. This research uses the Research and Development (R&D) method with the ADDIE development meodel (Analysis, Design, Development, Implementation, and Evaluation). The research was carried out at SMP Negeri 1 Air Putih, Dusun II Village of sipare-pare, Kecamatan Air Putih, Kabuppaten Batu Bara, North Sumatra. The subjects of this study were 23 students of class VII-5.The research instruments used are field study instruments in the form of observations and interviews, validation instruments as validation sheets, as well as practicality instruments such as responding sheets of students and teachers. The data analysis techniques used in this research are field study instance data analysis such as interview results, data analysis of validation of learning media and analysis of data practicality learning media.Based on the results of the evaluation by the material experts and media experts obtained the result that the learning media developed has an excellent level of validity. The level of validation obtained from 4 people material validator and 4 people media validator received highly valid criteria for validation of material with a presentation of 95.3% and included highly valid Criteria for media validation with presentations of 95,6% including into criteria very valid so that it can be said that the learning media developed is very worthy to use. At the stage of practicality performed by the pupils and teachers obtained an excellent level of practicability with presentations from pupils of 92% and presentations of teachers of 100% so it can be said that the learning media developed into the criteria very practical. The conclusions of this study show that the android-based mathematical learning medium on the built-up material of the space that has been generated is very valid and very practical so that it can be used in the learning process.